A survey on Flickr multimedia research challenges. (May 2016) - Spyrou, Evaggelos; Mylonas, Phivos
Abstract: Multimedia content sharing within social networks has become one of the most interesting and trending research fields over the last few years. This undoubted emerge of related research works is rather twofold, namely it includes both the analysis and management techniques of the content itself, as well as new ways for its accompanied meaningful interpretation and exploitation. In this paper, we review the recent advances in the above fields in the humanistic framework of the popular Flickr social network. In addition, the major research challenges in the area are demonstrated and discussed, which include current state-of-the-art approaches with respect to interesting humanistic data collection and interpretation research fields, such as multimedia information retrieval, (semi-) automatic tag manipulation, travel applications, semantic knowledge extraction, human activity tracking, as well as related benchmarking efforts. At the end of this survey, we also discuss the main challenges and propose a number of future research directions for interested fellow researchers to continue investigation in the field.